Beyond standard rehabilitation programmes: Working with people with MS for adequate goal setting and rehabilitation treatment evaluation. (September 2019) - Playford, E Diane
Shared decision-making occurs when the decision is 'preference sensitive'. It consists of identifying the different treatment options (choice talk), considering the advantages and disadvantages of each option (option talk), and then supporting making the decision in the light of an individual's experiences and values (decision talk). It is most effective when working with an 'activated patient', that is, one who is prepared for the shared decision-making role. In rehabilitation, many decisions are preference sensitive. These decisions may be framed as 'goal setting'. Skilled clinicians can support patients to learn goal setting skills until the person has the skills to maintain health supporting behaviours most of the time, only seeing a clinical team at times of change or crisis. The steps in goal setting can be summarised as building empathy, creating a contract, identifying priorities, summarising the conversation, articulating the goal, defining actions, building coping plans, and then reviewing progress. Working with people with MS can extend beyond working with individuals to a consideration of what people with MS want from services. This can result in the co-production and co-design of services, as well as the identification of research priorities as exemplified by the James Lind Alliance.